2004
DOI: 10.1002/app.20704
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of the refractive index of poly(methyl methacrylate) with a nitrone additive

Abstract: Hydroxy-substituted aromatic nitrone derivatives were used for the photochemical control of the refractive index of poly(methyl methacrylate) (PMMA) films. Upon irradiation with 366-nm light in solution, these derivatives underwent rearrangement reactions, which eventually produced N,N-diarylformamide derivatives in quantitative yields. Similar photoreactions of the aromatic nitrones in the PMMA films lowered the refractive index of the films by as much as 0.014. The magnitude of the observed refractive-index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Miyata et al 23 reported that 4-N,N-dimethylaminophenyl-N-phenyl nitrone doped in poly-(methyl methacrylate) films showed Án D 's of 0.026-0.028. Sakurai et al [24][25][26][27][28] found that films containing certain nitrone derivatives showed Án D 's of 0.014-0.023 upon photo-isomerization. Knol and Müllen 29,30 showed that polymers with pendant 9-substituted anthracene (AT) had large Án D 's in the range of 0.013 to 0.076 upon photo-dimerization of AT.…”
Section: Calixarene Derivatives As Refractive-index-changing Materialsmentioning
confidence: 99%
“…Miyata et al 23 reported that 4-N,N-dimethylaminophenyl-N-phenyl nitrone doped in poly-(methyl methacrylate) films showed Án D 's of 0.026-0.028. Sakurai et al [24][25][26][27][28] found that films containing certain nitrone derivatives showed Án D 's of 0.014-0.023 upon photo-isomerization. Knol and Müllen 29,30 showed that polymers with pendant 9-substituted anthracene (AT) had large Án D 's in the range of 0.013 to 0.076 upon photo-dimerization of AT.…”
Section: Calixarene Derivatives As Refractive-index-changing Materialsmentioning
confidence: 99%
“…[1][2][3] Recently, much attention has been devoted to the photochemical control of refractive indices for polymer films, owing to their potential in optical network technology. 3 Although there are extensive studies directed toward a photoinduced decrease in refractive indices for polymer films, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] only a few attempts have been made to enhance the refractive index through photochemical transformations. 12,[20][21][22][23][24][25] For example, Langer et al 21 reported that irradiation of a polymerbearing thiocyanate pendants enhanced the refractive index (n) of the polymer by 0.031.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] These photoreactive groups showed changes of π-electron system after photoirradiation, with decreased R values.…”
Section: Introductionmentioning
confidence: 99%